Functional Outcome of Hooked/Locked Patellar Plate Versus Tension Band Wiring in Treatment of Patellar Fractures: A Comparative Case Series - Jaffer Jawad, Mohammed; Abbas Saadoon, Raed; Nori, Wassan (Scripta Medica, 2026)
Background/Aim: Patella fractures significantly compromise the knee joint function and usually require surgical fixation to restore the knee extensor mechanism. Tension band wiring (TBW) and locked patellar plate (LPP) are widely used surgical methods for the fixation of these fractures. With in 12-months post-surgery functional outcome using Lysholm knee score (LKS) as primary outcome and visual analog score (VAS) were compared, degree of knew flexion, complication and radiographic union as a secondary outcome.Methods: Prospective comparative case series consecutively enrolled 24 patients with patella fractures allocated by chosen fixation method into: TBW (12/24) group and hooked part of the locked patellar plate (H/LPP) group (12/24). Patients’ demographics, fractures criteria, 12-months LKS and 12-month VAS were recorded in addition to other secondary parameters (operative time, radiographic union, complication).Results. At 1-year follow-up, mean LKS was significantly higher in H/LPP group vs TBW group (89.4 ± 4.8 vs 79.2 ± 6.5; p = 0.0016). The VAS scores were lower in H/LPP than TBW group (1.8 ± 0.9 vs 3.1 ± 1.2; p = 0.0042). Radiographic union time showed trend in H/LPP vs TBW group (10.3 ± 1.5 vs 11.2 ± 1.8 weeks; p = 0.125). Complications occurred in 4 (33.3 %) of TBW group (one wire breakage, 2 patients with k-wire prominence and superficial infection) but only one patient (8.3 %) had implant related discomfort as a complication which resolved spontaneously was seen in LPP group, p = 0.093. Conclusion: H/LPP fixation demonstrates superior functional outcomes, lower pain scores and fewer complications compared to TBW in the treatment of patella fractures, making it a recommendable option for patellar fracture management.
Keywords: Patella fracture; Tension band wiring; Hooked/locked patellar plate; Lysholm knee score; Visual analog scale; AO/OTA fracture and dislocation classification